The Influence of the Islamic Social Environment in Developing Children's Creativity: A Case Study of Maestro Architect Achmad Noe'man - Utama, Muhammad Rizki; Zakaria, Mumuh Muhsin; Mulyadi, Raden Muhammad (International Journal Pedagogy of Social Studies, 2023)
The purpose of this paper is to discuss the influence of Islamic socialenvironment such as extended and nuclear family, Muslimcommunity social movement, and non-formal education in order todevelop children's creativity in the case of the maestro architectAchmad Noe'man's childhood life. The research would employ thehistorical method with the multiple intelligence theory approach.Achmad Noe'man is an early generation Indonesian architect whowas the first architect to graduate from the Faculty of Engineering,University of Indonesia Bandung (now ITB) in 1958. He was one ofthe founders of the Indonesian Architect Association (IAI). At theyoung age, he successed to design the Salman Mosque of ITB, calleda milestone in modern mosque architecture and has even becomeone of the world's contemporary mosques. He passed away in 2016after practicing as an architect for more than 50 years with the tittlethe architect of a thousand mosques and the maestro of mosquearchitecture in Indonesia. This study will attempt to describe howthe role of the social environment around Noe'man formed hispersonality which will later encourage him to become a creativeperson.